The differences between 14-16 year-old tennis players and the most successful tennis players of the same age respectively based on basic motor skills - Separovic, V.; Babajic, F.; Mulahasanovic, M. (Sportski Logos, 2017)
The main aim of this research was to confirm the existence of differences between tennis players and the most successful tennis players aged 14-16, established on basic motor skills using scientific methods. Sixteen tennis players aged 14-16 participated in this research. The variables sample consisted of 14 tests that were divided into three motor areas: area of explosive power (5 tests), area of agility and coordination (3 tests) and area of balance and proprioception (6 tests). T-test was applied on certain motor dimensions for individual samples in order to verify the presence of differences between young and promising tennis players in B&H and their peers. The results obtained from this research show that there is a statistically valuable distinction between tennis players and the most successful tennis players aged 14-16 in almost all variables of basic motor skills. The analysis of results confirmed that the best tennis player represents a role model. These findings can be beneficial for his coach whereas the other coaches can also use them to focus on the ways to improve and aim their training-oriented activities in the right direction.